Kinetic molecular sieving, thermodynamic and structural aspects of gas/vapor sorption on metal organic framework [Ni1.5(4, 4′-bipyridine)1.5(H3L)(H2O)3][H2O]7 where H6L = 2, 4, 6-trimethylbenzene-1, 3, 5-triyl tris(methylene)triphosphonic acid. Issue 4 (7th January 2016) - Zhao, Xuebo; Bell, Jon G.; Tang, Si-Fu; Li, Liangjun; Thomas, K. Mark
Abstract : A phosphonate based MOF was synthesized, the structure determined and gas/vapor adsorption characteristics studied. Abstract : A metal organic framework [Ni1.5 (4, 4′-bipy)1.5 (H3 L)(H2 O)3 ]·[H2 O]7 where H6 L = 2, 4, 6-trimethylbenzene-1, 3, 5-triyl tris(methylene)triphosphonic acid and 4, 4′-bipy = 4, 4′-bipyridine has been prepared. The structures of [Ni1.5 (4, 4′-bipy)1.5 (H3 L)(H2 O)3 ]·[H2 O]7 and the desolvated form [Ni1.5 (4, 4′-bipy)1.5 (H3 L)(H2 O)3 ] have been determined by single crystal X-ray diffraction and the framework structures are virtually identical with the former having disordered water molecules in the pores. The framework structure comprises of two-dimensional Ni1.5 (H3 L) layers and 4, 4′-bipy linkers acting as pillars with an unusual framework topology of a (3, 3, 6) net that can be denoted as: 4·6 2 2 6 3 2 6 8 ·8 5 ·10 2 . The framework has one-dimensional channels decorated with acidic O–H groups with irregular shape varying from narrow windows (cross section: 4.2 × 4.2 Å) to pore cavities (diameter: ∼12 Å). Thermogravimetric studies showed that both coordinated and lattice water molecules adsorbed in pores were removed in ultra-high vacuum to give [Ni1.5 (4, 4′-bipy)1.5 (H3 L)]. The water vapor adsorption isotherm for [Ni1.5 (4, 4′-bipy)1.5 (H3 L)] showed that 3 coordinated and ∼7 pore lattice water molecules were adsorbed and the framework structure was reformed. The desorption isotherm showed that the lattice water was easily desorbed in vacuum at 20 °C to form [Ni1.5 (4, 4′-bipy)1.5 (H3 L)(H2 O)3 ]. The ethanol adsorption isotherms for [Ni1.5 (4, 4′-bipy)1.5 (H3 L)] for temperature range 20–50 °C were markedly hysteretic. The stoichiometry was [Ni1.5 (4, 4′-bipy)1.5 (H3 L)]·[1.11C2 H5 OH] at p / p 0 = 0.97 and 20 °C gave a total pore volume approximately half that of [Ni1.5 (4, 4′-bipy)1.5 (H3 L)(H2 O)3 ]. The desorption isotherms show that ethanol is strongly retained with decreasing pressure indicating a stable framework structure. The kinetic profiles for oxygen, nitrogen, carbon dioxide, and water and ethanol vapors, can be described by Fickian, combined barrier resistance/diffusion (CBRD), and stretched exponential models for both adsorption and desorption. Gas adsorption studies for [Ni1.5 (4, 4′-bipy)1.5 (H3 L)] reveal kinetic molecular sieving occurs with very high kinetic selectivity for O2 /N2 at 0 °C. Carbon dioxide adsorption has intermediate rates of adsorption between oxygen and nitrogen. The isosteric enthalpy for CO2 adsorption at zero surface coverage was 30.7 ± 2.4 kJ mol −1 . The corresponding activation energy for diffusion of CO2 into the framework was ∼48 kJ mol −1 . Narrow constrictions in the porous structure of [Ni1.5 (4, 4′-bipy)1.5 (H3 L)] give rise to kinetic molecular sieving effects and do not allow adsorption of molecules such as methane, which has a larger cross-section. The selectivity for CO2 /CH4 was very high (x1000) at 30 °C. The adsorption results are discussed in terms of diffusion, thermodynamics and surface interactions in pores.